Realization of transistors using organic electronics - Ng, Vincent Yi Kai. (2013)
The overall objectives of this project are to investigate and realize printed electronics on flexible substrates. Specifically, this project focuses on the realization of organic transistors and a proto-type dual-gate transistor to verify the reliability and lifetime of OTFT due to the presence of the top dielectric layer. Concurrently, circuit simulation of AMOLED backplane driver is done to validate the design.